2016
DOI: 10.1155/2016/7031397
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Polyphenol Epigallocatechin Gallate Protects Intervertebral Disc Cells from Oxidative Stress

Abstract: Oxidative stress-related phenotypic changes and a decline in the number of viable cells are crucial contributors to intervertebral disc degeneration. The polyphenol epigallocatechin 3-gallate (EGCG) can interfere with painful disc degeneration by reducing inflammation, catabolism, and pain. In this study, we hypothesized that EGCG furthermore protects against senescence and/or cell death, induced by oxidative stress. Sublethal and lethal oxidative stress were induced in primary human intervertebral disc cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 75 publications
2
60
0
Order By: Relevance
“…EGCG inhibited the expression of inflammatory markers (IL-6, IL-8, PTGS2, TLR2, and iNOS), collagenases (MMP1, MMP3, and MMP13) and NGF in human IVD cells cultured adherently and in alginate beads [11]. EGCG also protected IVD cells from oxidative stress caused by exogenous radicals [37] and, moreover, locally delivered EGCG reduced radicular pain in a rat model of NP herniation [11]. Therefore, we selected this compound for validation of the new inflammation-induced NP culture model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG inhibited the expression of inflammatory markers (IL-6, IL-8, PTGS2, TLR2, and iNOS), collagenases (MMP1, MMP3, and MMP13) and NGF in human IVD cells cultured adherently and in alginate beads [11]. EGCG also protected IVD cells from oxidative stress caused by exogenous radicals [37] and, moreover, locally delivered EGCG reduced radicular pain in a rat model of NP herniation [11]. Therefore, we selected this compound for validation of the new inflammation-induced NP culture model.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds derived from traditional medicinal plants act on several signal transduction and apoptotic cascades at the same time, while having minimal side effects [33]. We have shown before that natural compounds such as resveratrol [34], curcumin [35], triptolide [36] and epigallocatechin 3-gallate (EGCG) [11,37] exhibit anti-inflammatory, anti-catabolic and anti-oxidant activity in disc cells. Although more research is needed to fully understand the effects of these compounds on the integrity of the IVD, it has been suggested that they can delay degeneration of the NP or even reverse it.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 resulted in a rapid increase in ROS production and DNA damage in human NP cells. Consequently, the ATM-Chk2-p53-p21-Rb pathway and the p16-Rb pathway were activated to induce premature senescence of human NP cells [15, 34]. H 2 O 2 also induced premature senescence of human CEP cells through the p53-p21-Rb pathway [91].…”
Section: The Roles Of Oxidative Stress In the Pathogenesis Of Iddmentioning
confidence: 99%
“…Polyphenol epigallocatechin 3-gallate is a polyphenol redox scavenger. In vitro investigations have found that polyphenol epigallocatechin 3-gallate not only suppresses the senescence and apoptosis of human NP cells under oxidative stress, but also inhibits the expression of cytokines and MMPs in human NP cells through regulating the MAPK pathway and the NF- κ B pathway [34, 35]. …”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Primary cells were isolated from human IVD biopsies from patients undergoing spinal surgery (approved by the ethical committees in Zurich and Lucerne, Switzerland, and after informed consent), as previously described [32]. For patient demographics, see Table 1.…”
Section: Cell Isolation and Culturementioning
confidence: 99%